Bukan Allah yang “Mengabulkan”: Telaah terhadap Pemilihan Kata “Mengabulkan” sebagai Terjemahan ἀκούει dalam 1 Yohanes 5:14-15 - Rouw, Randy Frank; Rikson, Juan; Luthy, Christopher James (Integritas: Jurnal Teologi, 2023)
In this article, the authors analyze the choice of the word "grant" in 1 John 5:14-15 as the translation of the word ἀκούει. The authors argue that the word "grant" is a poor translation choice because it has nothing to do with granting prayer. Using a descriptive qualitative method, the authors identify several arguments that require the use of the word "grant" in Terjemahan Baru to be reviewed. Specifically, the authors argue that the use of the word "grant" in 1 John 5:14-15 can mislead readers into understanding God as a God who will definitely grant prayers.